2014
DOI: 10.1016/j.jaci.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase 1/3 signaling pathways are key initiators of TH2 differentiation and lung allergic responses

Abstract: Background Janus kinases (JAK) are regulators of signaling through cytokine receptors. The importance of JAK1/3 signaling on Th2 differentiation and development of lung allergic responses has not been investigated. Objective To examine a selective JAK1/3 inhibitor (R256) on differentiation of Th subsets in vitro and on development of ovalbumin (OVA)-induced airway hyperresponsiveness (AHR) and inflammation in an experimental model of asthma. Methods A selective JAK1/3 inhibitor was used to assay the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…There has been concern that blocking JAK2 may have inhibitory effects on hematopoiesis, so there has been a search for more selective inhibitors. JAKs play a key role in differentiation of Th2 cells and a JAK1/3 inhibitor (R256) blocked the differentiation of Th2 cells and the phosphorylation of STAT5 and STAT6, but not of Th1 or Th17 cells in vitro (Ashino et al, 2014). In vivo R256 inhibited allergic inflammation, AHR, and mucus hypersecretion in a mouse model without any changes in Th2 cytokine concentrations.…”
Section: Janus-activated Kinase Inhibitionmentioning
confidence: 99%
“…There has been concern that blocking JAK2 may have inhibitory effects on hematopoiesis, so there has been a search for more selective inhibitors. JAKs play a key role in differentiation of Th2 cells and a JAK1/3 inhibitor (R256) blocked the differentiation of Th2 cells and the phosphorylation of STAT5 and STAT6, but not of Th1 or Th17 cells in vitro (Ashino et al, 2014). In vivo R256 inhibited allergic inflammation, AHR, and mucus hypersecretion in a mouse model without any changes in Th2 cytokine concentrations.…”
Section: Janus-activated Kinase Inhibitionmentioning
confidence: 99%
“…The analysis of STAT6-deficient mice has demonstrated that the vast majority of IL-4-induced responses are indeed mediated through the JAK-STAT pathway (Chitnis and Khoury, 2003;Kiu and Nicholson, 2012), and JAK/STAT pathway plays a critical role in the differentiation of Th2 cells (Ashino et al, 2014). JAKs are regulators of signaling through cytokine receptors, among which JAK1 and JAK3 play critical roles in the initiation of inflammation and have been investigated as potent therapeutic targets in a variety of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…JAKs are regulators of signaling through cytokine receptors, among which JAK1 and JAK3 play critical roles in the initiation of inflammation and have been investigated as potent therapeutic targets in a variety of inflammatory diseases. A selective JAK1/3 inhibitor inhibited differentiation of Th2 cells, down-regulated STAT6 and STAT5 phosphorylation and prevented the development of AHR, airway eosinophilia, mucus hypersecretion, and Th2 cytokine production (Ashino et al, 2014). STAT6 has been demonstrated to regulate many pathologic features of lung inflammatory responses in animal models including airway eosinophilia, epithelial mucus production, smooth muscle changes, Th2 cell differentiation, and IgE production from B cells (Walford and Doherty, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations